2010
DOI: 10.1592/phco.30.11.1127
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Health Care Expenditures After Enrollment in a Collaborative Cardiac Care Service

Abstract: The comprehensive and aggressive implementation of secondary cardiac prevention strategies and close monitoring and follow-up of patients with coronary artery disease provided by the CCCS were associated with reduced health care expenditures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 22 publications
(29 reference statements)
0
9
0
Order By: Relevance
“…Prior studies defined cost avoidance as a measure of reduced health care use (ie, reduced readmission, physician visits, clinical events, etc), reduced direct medication costs to patients, or both. 11,12,29 Our study, which is one of few to evaluate pharmacist impact in an outpatient cardiology setting and the only one highlighting the role in a preventive cardiology practice, evaluated both outcomes as well, in the form of cost avoidance related to clinical interventions and cost avoidance from patient out-of-pocket expense reduction. Interestingly, the cost avoidance strategies from patient out-of-pocket expense reduction only represented 7% of the pharmacist interventions but accounted for 82% of the aggregate cost reduction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies defined cost avoidance as a measure of reduced health care use (ie, reduced readmission, physician visits, clinical events, etc), reduced direct medication costs to patients, or both. 11,12,29 Our study, which is one of few to evaluate pharmacist impact in an outpatient cardiology setting and the only one highlighting the role in a preventive cardiology practice, evaluated both outcomes as well, in the form of cost avoidance related to clinical interventions and cost avoidance from patient out-of-pocket expense reduction. Interestingly, the cost avoidance strategies from patient out-of-pocket expense reduction only represented 7% of the pharmacist interventions but accounted for 82% of the aggregate cost reduction.…”
Section: Discussionmentioning
confidence: 99%
“…well positioned to help fill the chronic disease management gap and make a difference when they are actively engaged as part of a team-based care approach.” 2 Ample evidence supports the value of pharmacist intervention in improving outcomes, medication adherence, and cost in the ambulatory care setting. 3,7-14 A key determinant of these improved outcomes relates to increased access to medications, influenced significantly by patient out-of-pocket medication expense. 15-18 In that regard, the objective of this study was to describe the impact of interventions initiated by a clinical pharmacist within a preventive cardiology clinic, with an emphasis on patient cost avoidance.…”
Section: Introductionmentioning
confidence: 99%
“…Cost-effectiveness has been found to be strongly dependent on parameters such as the age of the target population, the overall population risk of CV diseases, and the interventions' cost [2]. Delate and colleagues retrospectively evaluated the financial impact of a comprehensive cardiac care service program from the perspective of their health plan [23]. They found that when patients were assisted by a collaborative cardiac care service (a multidisciplinary program co-managed by clinical pharmacy, specialist, and nurses), inpatient and outpatient hospitalizations, and medical office visits, were associated with lower healthcare resource utilization and costs.…”
Section: Healthcare Integrated Costsmentioning
confidence: 99%
“…13,15,17,25,36,40,47 On the basis of disease or type of condition, diabetes mellitus was the most frequently studied (n = 11). d Other conditions that were commonly studied included cardiovascular disease (n = 7), 16,17,36,40,47,66,69 mental health and substance abuse (n = 6), 26,30,32,45,57,67 and asthma/chronic obstructive pulmonary disease (n = 4). 16,22,35,68 Several themes emerged from the literature as possible factors that may contribute to improved care delivery in integrated delivery systems.…”
Section: Review Articlementioning
confidence: 99%